PENGARUH MEDIA SOSIAL TERHADAP GAYA PENGASUHAN MILLENIAL PARENT - Haniati Gowasa (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to understand how social media influences the parenting styles of millennial parents in Indonesia, given the limited research specifically addressing this phenomenon. Using a qualitative method with an Interpretative Phenomenological Analysis (IPA) approach, the study involved eight millennial parents selected through purposive sampling, characterized by their active use of platforms such as Instagram, TikTok, and YouTube. Data were collected through in-depth interviews, non-participant observation, digital documentation, and field notes, and were analyzed using IPA stages combined with the data reduction and display techniques of Miles & Huberman. The findings reveal four main themes: social media as a primary source of parenting knowledge; the construction of identity as modern parents; the implementation of parenting practices based on digital content; and emerging challenges such as anxiety, social comparison, and confusion due to the abundance of diverse information. Social media is shown to play an ambivalent role—both empowering and pressuring depending on parents’ digital literacy in filtering and interpreting information. This study is expected to contribute to the development of digital communication studies, parenting research, and family education policy, while encouraging a more critical, healthy, and contextual use of social media in parenting practices.